PENGARUH STORE ATMOSPHERE TERHADAP MINAT PEMBELIAN ULANG MELALUI KEPUASAN PELANGGAN DI PUSAT GROSIR SUKARAMAI TRADE CENTER PEKANBARU - Setiawan, Faldino; Marnis, Marnis; Wijayanto, Gatot (Ikatan Sarjana Ekonomi Indonesia Cabang Pekanbaru, 2024)
This study aims to see and determine the direct and indirect effects of store atmosphere on repurchase intention through customer satisfaction at the Pusat Grosir Sukaramai Trade Center Pekanbaru. The research approach used in this study is a quantitative approach. In this study the population is consumptive customers or customers who buy for personal consumption at the Pusat Grosir Sukaramai Trade Center (STC). The sample used Hair et al, so the number of samples in this study is an indicator of the research variables as many as 16 pieces plus the number of hypotheses of 4, and then multiplied by 5 so that the sample obtained is 100 respondents. For the sampling technique that is using simple random sampling, where sampling is done randomly using SEM analysis. The results in this study are that store atmosphere has a significant effect on repurchase intention through customer satisfaction. atmosphere and customer satisfaction have a significant influence on repurchase intention. Customer satisfaction is able to mediate the effect of store atmosphere significantly on repurchase intention. Keywords: Store Atmosphere, Customer Satisfaction and Repurchase Intention